Aspirations to grow: When micro- and informal enterprises in the street food sector speak for themselves - A. J. Knox; Hans Th. A. Bressers; Nthabiseng Mohlakoana; J. De Groot (Journal of Global Entrepreneurship Research, 2019)
The street food sector in Sub-Saharan Africa is a source of affordable and nutritious meals for the urban poor, while also being an important source of income for the women who dominate this sector. Despite the importance of this sector, many micro- and informal enterprises are labelled as 'survivalist', beyond the reach of common development policies, which give priority to so-called growth-oriented enterprises. When given the chance to speak for themselves, do enterprises express any aspirations to grow? Contrary to the literature, our findings show that necessity-driven enterprises do aspire to grow and that this is true for both those owned by men and women. Using contextual interaction theory, this paper explains why it is possible for previous authors to come to such a different conclusion.
Keywords: 650; Gender; Entrepreneurship; Survivalist; Growth oriented; Informal